Executive Function Moderates the Relation between Coping and Depressive Symptoms - Morris, Matthew C. (Anxiety Stress Coping, 2014)
BACKGROUND AND OBJECTIVES: Identifying risk factors early in the course of depression has important implications for prevention, given that the likelihood of recurrence increases with each successive episode. DESIGN: This study examined relations among coping, executive functioning, and depressive symptom trajectories in a sample of remitted-depressed (n = 32) and never-depressed (n = 36) young adults (ages 18 to 31). METHODS: Participants completed a clinical interview, a measure of coping, and tasks assessing two components of executive function -- inhibition and cognitive flexibility. Participants were re-assessed regarding the timing and severity of depressive symptoms that had occurred during the interval period (mean = 35.16 weeks, SD = 9.03). RESULTS: Among never-depressed individuals, less primary control coping (e.g., problem-solving) and greater disengagement coping (e.g., avoidance) predicted increases in depressive symptoms. Greater secondary control coping (e.g., acceptance) predicted decreases in depressive symptoms and was unrelated to depression history. Higher inhibition scores predicted less increase in depressive symptoms for individuals reporting less primary control coping or more disengagement coping. Higher cognitive flexibility scores predicted less increase in depressive symptoms among individuals reporting less secondary control coping. CONCLUSIONS: Interventions aiming to enhance either coping strategies or executive functions may reduce risk for depression recurrence.